Drug Use Pattern Between Urban Families in Ardabil City, Iran - Shohreh Sarrafe Smaeili; Negar Alaaf Akbari; Mohammad Sadegh Soltan Mohaammadzadeh; Afshin Shaker; Firuz Amani (Tehran University of Medical Sciences, 2012)
Background and Aim: Medicine as a strategic commodity and basic needs of the most people in the country is important. According to the necessary recognition correct pattern of drug use, this study is conducted to measure the pattern of drug use among Ardabil city families. Materials and Methods: A cross -sectional descriptive study was conducted on 1000 randomly selected families from Ardabil city in 2010. Necessary information was gathered by interviewing one of the oldest people in the family. Collected data was analyzed using descriptive statistical methods in SPSS.16 software. Results: 485(48.5%) of study people were female and rest of them were male. The mean age of samples was 41.6(SD=14.1). From all families 22% uses the drugs in home for curing diseases by self diagnosis. 10.9% of them do not respond to doctors non medical advice and prefer the doctor to prescribe drugs otherwise they refer to another doctor. Conclusion: Results showed that the drug use behavior between Ardabil city families was inappropriate and decreasing irrational use of drugs by providing necessary information to people regarding optimal use of medicine was necessary.